PENYARINGAN KANDIDAT UNTUK PROMOSI JABATAN DENGAN PROFILE MATCHING - Palandi, Jozua F.; Pudyastuti, Zusana E. (DINAMIKA DOTCOM, 2014)
Management of Human Resource Development affects all of many aspects to determine the success of an organizations work. This research is intended to provide a decision support for Human Resources Development in terms of promotion. Determining a candidate for promotion takes a long time and requires an objective and transparent perspective. Filtering a candidate using a mixed system, a filtering system based on the administrative and personal assessment, is considered not objective. It will lead to subjective result since interview is used for conducting personal assessment.An application to select the candidate is important to be made in order to overcome the problem. The objective of the application is to assist the management in giving assessment, analyzing, formulating, and making decision. The output is a system for assessing the performance of the employee in term of promotion in an organization.The application will result an easier and more objective assessment in assisting the management to filter an employee to be promoted. This research, specifically, used variable parameter, while the method used in this research is profile matching method.Â Keyword: Promotion, Profile Matching, Human Resources